High Prevalence of Insecure Attachment in Patients with Primary Hypertension - Balint, Elisabeth M.; Gander, Manuela; Pokorny, Dan; Funk, Alexandra; Waller, Christiane; Buchheim, Anna (Frontiers in Psychology, 2016)
Hypertension is a major cardiovascular (CV) risk factor and is predicted by heightened CV reactivity to stress in healthy individuals. Patients with hypertension also show an altered stress response, while insecure attachment is linked to a heightened stress reactivity as well. This is the first study aiming to assess attachment representations in patients with primary hypertension and to investigate their CV responses when their attachment system is activated. We studied 50 patients (38 men, 12 women) with primary hypertension. The Adult Attachment Projective Picture System (AAP), a widely used and validated interview, was performed to measure the patients’ attachment representations, and to activate their attachment system. Blood pressure and heart rate were measured after ten minutes at rest prior to and directly after the AAP interview. Mood and state anxiety were assessed using the Multidimensional Mood State Questionnaire (MDBF) and the State Trait Anxiety Inventory – State (STAI-S) before and after the experiment. The prevalence of insecure attachment (dismissing, preoccupied, unresolved) in hypertensive patients was predominant (88%), while in non-clinical populations, only about 50% of individuals had insecure attachment patterns. Blood pressure (p<.001), heart rate (p=.016) and rate pressure product (p<.001) significantly increased in response to the attachment interview. Secure attached patients showed the highest rise in systolic blood pressure (p=.020) and the lowest heart rate compared to the other attachment groups (p=.043). However, attachment representation showed no significant group or interaction effects on diastolic blood pressure and rate pressure product. Insecure attachment was highly over-represented in our sample of patients with primary hypertension. Additionally, a robust CV response to the attachment-activating stimulus was observed. Our data suggest that insecure attachment is significantly linked to primary hypertension, which implies the need for further investigations to evaluate attachment insecurity as a possible risk factor for hypertension.